Two Acinetobacter baumannii Isolates Obtained From a Fatal Necrotizing Fasciitis Infection Display Distinct Genomic and Phenotypic Characteristics in Comparison to Type Strains - Grier, Jennifer T.; Arivett, Brock A.; Ramírez, Maria S.; Chosed, Renee J.; Bigner, Jessica A.; Ohneck, Emily J.; Metz, Maeva L.; Wood, Cecily R.; Arce, Sergio; Tartaro, Andrea; Relich, Ryan F.; Actis, Luis A.; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Acinetobacter baumannii has been recognized as a critical pathogen that causes severe infections worldwide not only because of the emergence of extensively drug-resistant (XDR) derivatives, but also because of its ability to persist in medical environments and colonize compromised patients. While there are numerous reports describing the mechanisms by which this pathogen acquires resistance genes, little is known regarding A. baumannii’s virulence functions associated with rare manifestations of infection such as necrotizing fasciitis, making the determination and implementation of alternative therapeutic targets problematic. To address this knowledge gap, this report describes the analysis of the NFAb-1 and NFAb-2 XDR isolates, which were obtained at two time points during a fatal case of necrotizing fasciitis, at the genomic and functional levels. The comparative genomic analysis of these isolates with the ATCC 19606T and ATCC 17978 strains showed that the NFAb-1 and NFAb-2 isolates are genetically different from each other as well as different from the ATCC 19606T and ATCC 17978 clinical isolates. These genomic differences could be reflected in phenotypic differences observed in these NFAb isolates. Biofilm, cell viability and flow cytometry assays indicate that all tested strains caused significant decreases in A549 human alveolar epithelial cell viability with ATCC 17978, NFAb-1 and NFAb-2 producing significantly less biofilm and significantly more hemolysis and capacity for intracellular invasion than ATCC 19606T. NFAb-1 and NFAb-2 also demonstrated negligible surface motility but significant twitching motility compared to ATCC 19606T and ATCC 17978, likely due to the presence of pili exceeding 2 µm in length, which are significantly longer and different from those previously described in the ATCC 19606T and ATCC 17978 strains. Interestingly, infection with cells of the NFAb-1 isolate, which were obtained from a premortem blood sample, lead to significantly higher mortality rates than NFAb-2 bacteria, which were obtained from postmortem samples, when tested using the Galleria mellonella in vivo infection model. These observations suggest potential changes in the virulence phenotype of the A. baumannii necrotizing fasciitis isolates over the course of infection by mechanisms and cell processes that remain to be identified.